A rational basis for a new scoring system measuring disability in Parkinson’s disease - Baas, Horst; Stecker, K.; Bergemann, Niels; Fischer, Peter-Alexander (Instrumental methods and scoring in extrapyramidal disorders, 1995)
For the quantitative assessment of disability in Parkinson’s disease (PD), a number of rating scales (RS; Alba et al. [1], Birkmayer et al. [4], Canter et al. [6], Duvoisin [9], Gerstenbrand et al. [12], Hoehn et al. [15], Markham et al. [22], Schwab et al. [26], Webster [32], Yahr et al. [33]) have been introduced and are used just like the numerous apparative tests (AT; [7,8,13,17,19,20,23-25,30]). Each of them has its specific advantages, disadvantages, and limitations. In particular, the adequate use of RS is limited by the fact that they are restricted to the ordinal data level, permitting only nonparametric statistics, and by the large number of items and poor interrater reliability. In contrast, the use of AT is limited by higher costs, sometimes by the need of sophisticated technical equipment, the registration of only partial aspects of complex PD symptomatology, and time-consuming procedures.
Gesehen am 14.12.2020